THE VALUE ADDED PROCESSING MUSHROOMS FLOUR INTO COOKIES AT CV ASSALAM CIANJUR WITH BUSINESS MODEL CANVAS (BMC) APPROACH - Doni Sahat Tua Manalu; Gustiya Kevin Nugrahaini; Nurinda Utami Padoma (AgriDev, 2023)
CV Assalam is a company engaged in the cultivation of oyster mushrooms and produces mushroom flour as one of its products. The most popular flour derivative products are cookies. This is an opportunity for CV Assalam to produce cookies in order to gain added value and increase the company's revenue. The objectives of the research are 1) to formulate and review a business plan for oyster mushroom cookies at CV Assalam with the BMC approach, 2) to analyze the financial impact of the oyster mushroom cookies business on CV Assalam. The research method was the data source using primary and secondary data and descriptive analysis using the BMC approach. The results showed that processing oyster mushrooms into mushroom cookies is the right thing to do because it will get added value from mushroom products. CV Assalam must maximize product promotion through e-commerce and social media so that it is better known to the public. Based on financial analysis, it was found that processing mushroom flour into cookies could increase CV Assalam's net income by IDR 5,156,906/month.